PELATIHAN DIGITALISASI “MY DRIVE MY ARSIB” DALAM PENGELOLAAN ADMINISTRASI DI DESA TINGGARJAYA - Nasori, Ahmad; Aslindar, Dwi Astarani; Banani, Ade (STKIP Persada Khatulistiwa Sintang, 2024)
ABSTRACTThe purpose of this community service activity is to improve services to the public in digital-based administrative management, so that the community can more easily and quickly access services. The method of implementing activities to find solutions to the administrative management issues in Tinggarjaya Village is carried out through work procedures that support the realization of the creation of this system. Socialization regarding the importance of digital-based administrative management. Then, conduct planned, structured, and continuous training for partners on how to use and utilize